Preventing Children from Gambling as Perpetrators of Criminal Acts - Anwar Umar; Kristi Warista Simanjuntak; Kariadi Kariadi (Journal of Law Justice (JLJ), 2026)
This study aims to analyze whether the current criminal law formulation policy is adequate in tackling the development of gambling crimes, as well as to explain the applicable policies implemented in handling gambling cases, especially in the city of Sorong. The research method used is normative juridical by examining secondary data in the form of legislation, legal literature, and various related legal materials. The novelty of this research lies in its comprehensive analysis of the effectiveness of combining penal and non-penal approaches in combating child gambling at the regional police level, as well as mapping structural obstacles that have not been widely studied in previous research.   The results of the study show that police efforts to combat child gambling in Sorong City include a penal approach in the form of investigation, enforcement, and the application of criminal sanctions based on applicable legal provisions. Meanwhile, the non-penal approach is carried out through counseling, environmental supervision, and cooperation with the community to prevent the development of gambling practices. However, the effectiveness of both approaches still faces obstacles in the form of minimal coordination between law enforcement officials, local government, and the community, as well as high social tolerance for gambling practices. The conclusion of this study is that although a criminal law framework is in place, its implementation still requires strengthened inter-agency coordination, increased legal awareness, and an active role for the community to reduce gambling practices in a sustainable manner.